Cartografia da vulnerabilidade socioambiental: convergências e divergências a partir de algumas experiências em Portugal e no Brasil - Freitas, Maria Isabel Castreghini [UNESP]; Cunha, Lúcio (Pontifícia Universidade Católica do Paraná (PUC-PR), 2013)
In this study we intent to contextualize the topic environmental vulnerability on the world stage, highlighting similarities and differences in their conceptions in Portugal and Brazil. In the literature about the vulnerability is already established the contribution of Geotechnologies, especially the Systems of Remote Sensing and Orbital Imaging as well as Geographic Information Systems (GIS) and its potential for modelling physical and socioeconomic aspects for the prevention, mitigation and facing risk manifestations, whether natural, technological or mixed. This paper aims to discuss the methodological framework of vulnerability studies and the results of application in the modelling of socioeconomic and environmental data in the context of the Region Centre of Portugal and the State of Sao Paulo, Brazil. The methodology for analysing the vulnerability of these regions was based on quantitative studies of the capacity of resistance and resilience of populations and territories. The results were consistent with the socio-environmental realities of the study areas and reflect the complexity of facing and recovery of risk situations in case of territories and populations under low economic conditions and urban infrastructure, whether in Brazil and Portugal.

Com este estudo, buscamos contextualizar o tema vulnerabilidade socioambiental no cenário mundial, destacando similaridades e discrepâncias nas suas concepções em Portugal e no Brasil. Na literatura que trata de vulnerabilidade já está consagrada a contribuição das Geotecnologias e do seu potencial para a modelagem de aspectos físicos e socioeconômicos, para a prevenção, mitigação e enfrentamento de manifestações de riscos, sejam eles naturais, tecnológicos ou mistos. Este artigo tem como objetivo discutir os referenciais metodológicos dos estudos de vulnerabilidade, bem como os resultados de aplicação na modelagem de dados socioeconômicos e ambientais no contexto da região Centro de Portugal e do estado de São Paulo, Brasil. A metodologia para a análise da vulnerabilidade dessas regiões baseou-se na avaliação quantitativa da capacidade de resistência e de resiliência de populações e de territórios. Os resultados apresentam-se coerentes com as realidades socioambientais das áreas de estudo e refletem a complexidade quando do enfrentamento e recuperação de situações de riscos para o caso de populações e territórios menos providos de condições econômicas e de infraestruturas urbanas, seja no Brasil ou em Portugal.
Cartography of the socio-environmental vulnerability: convergences and differences from some experiences in Portugal and Brazil
Keywords: Vulnerabilidade socioambiental; Cartografia; Metodologia quantitativa; Portugal; Brasil; Socio-environmental vulnerability; Cartography; Quantitative methodology; Portugal; Brazil